The First number of Journal Espiral, a journal on geography and social sciences - Germaná Cavero, César (2019)
ESPIRAL is aimed at the academy and the general public. We seek to promote academic production around geography and social sciences and become a space for dialogue, reflection and encounter. Likewise, we hope to debate theoretical positions, from the most diverse currents of thought, with a principle of solidarity, equity and reciprocity in the exchange of knowledge. The project seeks to accommodate the knowledge from popular knowledge, movements and social organizations, from the constant struggles for the defense of the territory and good living.